Penyuluhan Tentang Modal Dasar Berwirausaha Bagi Generasi Muda di Kelurahan Kekalik Jaya Kecamatan Sekarbela Kota Mataram - Irwan, M.; Salmah, Emi; Maryam, St.; Agustiani, Eka; Hidayat, M. Ali Akbar (Universitas Mataram, 2025)
This community service activity aims to enhance participants' understanding of the fundamental aspects of entrepreneurship, which include willingness, ability, knowledge, human capital, and entrepreneurial competence. The activity was conducted through interactive lectures supported by presentation slides. A total of 35 participants attended, exceeding the initial target, and consisted of entrepreneurs, youth, and university students. Participants actively engaged in the session by asking questions related to business planning and marketing systems. The results indicated that participants gained new insights into utilizing internal resources as entrepreneurial capital, along with the importance of material support. The success of the activity was reflected in the participants' enthusiasm and improved understanding. For future implementation, it is recommended that the service team provide follow-up training on starting a business, identifying business opportunities, and designing effective marketing strategies in increasingly competitive markets.